Original Short Stories $1 (BVolume 12s - Maupassant, Guy de, 1850-1893; Henderson, A. E.; McMaster, Albert Cohn; Quesada, Louise Charlotte Garstin (Salt Lake City, UT : Project Gutenberg, 2004)
"Original Short Stories $1 (BVolume 12" by Guy de Maupassant is a collection of compelling short stories written during the late 19th century. This volume includes a diverse array of narratives, exploring themes of love, loss, and human complexity through the lives of intricate characters such as M. Lemonnier, a widower navigating the challenges of fatherhood while grappling with the legacy of his deceased wife, and other figures embroiled in various emotional dilemmas. The opening of this collection introduces readers to the poignant story of "The Child," where M. Lemonnier, after the tragic death of his wife during childbirth, is left to parent their newborn son. His overwhelming love for the child is tinged with the haunting reminder of his wife's absence. The narrative progresses, revealing the complexities of father-son relationships, the tensions between love and responsibility, and the implications of social perceptions. As the story unfolds, we witness Lemonnier's denial of his son's possible paternity, stirred by the abruptness of his nurse's harsh truths, leading to a deeply emotional climax that sheds light on the fragility of human emotions. (This is an automatically generated summary.)s
The child -- A country excursion -- Rose -- Rosalie Prudent -- Regret -- A sister's confession -- Coco -- A dead woman's secret -- A humble drama -- Mademoiselle Cocotte -- The Corsican bandit -- The grave.
Some passages from the original French were omitted by the editor/translator in this English translation.
Release date is 2004-10-03
Produced by David Widger
Keywords: Short stories, French -- Translations into English